Implementasi E-Government dalam Pelayanan Publik Berbasis Website di Desa Tondowolio Kabupaten Kolaka - Muhammad Hidayat Djabbari; Irfan B.; Tri Cahyo Nugroho; Iswadi Amiruddin; Erwing Yanto (Kolaborasi : Jurnal Administrasi Publik, 2024)
The development of the digital era in Indonesia has driven the implementation of e-government in governmental management and public services. The purpose of this article is to analyze the implementation of web-based information systems in public services in Tondowolio Village using three main indicators: support, capacity, and value. This study employs a descriptive qualitative approach, focusing on these three key indicators. The research subjects include village officials, website managers, and community members who use the website services, with informants selected through purposive sampling. Data were collected through interviews, field observations, and document studies and then analyzed using the Interactive Model Analysis, which includes data reduction, data presentation, and conclusion drawing. The study's findings indicate that the support of village government, the availability of technological infrastructure, and adequate human resources are key factors in the success of e-government. However, challenges remain in the areas of regulation, socialization, and public understanding of web-based services. The implementation of e-government in this village has brought significant benefits in improving the efficiency and transparency of public services, although further efforts are needed to optimize its use by the entire community.